Pengaruh Strategi Pembelajaran Aktif Tipe Crossword Puzzle Berbantuan Media Flip Book Terhadap Keaktifan Belajar IPA Siswa Kelas IV Sekolah Dasar - Eka Febriyanti*; Mayarni Mayarni (Universitas Syiah Kuala, 2022)
The learning activities carried out in grade IV A and IV B elementary school in Bekasi were monotonous and teacher centered. It was marked by students who received only material without interaction with both teacher and peer, lack of courage in expressing opinions, asking questions, and answered questions so that student didn’t engage during learning. The research aims to see whether there is an impact on the active learning strategy, a type, a flip book with the activation of the study of grade IV student science. It employs a quantitative approach with a type of experimental quasi. The design used on this research is a non equivalent control group. Random samples were taken. The samples is students IV A and IV B at SDN Tridayasakti 03 with a total of 56. The instruments used are pretest and posttest of multiple choice, observation, and documentation. The data analysis consisted of normality test (shapiro wilk), homogeneity (fisher), and hypothesis (independent samples t-test) of a degree of = 0,05. The results of the hypothesis testing are obtained 7,112 1,683 and sig. (2-tailed) of 0,000 0,05 then is rejected and is accepted. This it can be concluded that the influence of active learning strategies is a typical, flip book type help against the science activation of the study the IV class of science students